Entrepreneurial university: a study at the Federal University of Fronteira Su - Rivaldo de Almeida Arruda; Humberto Tonani Tosta; Kelly Cristina Benetti Tonani Tosta (Revista Gestão Universitária na América Latina)
Objective: Mapping the actions promoting entrepreneurial education at the Federal University of Southern Frontier. Theoretical Framework: Entrepreneurial education initiatives, especially in Brazilian federal universities, need to be reviewed to bring not only regional economic development but also sustainable social development. Method: This article is characterized as a case study that employs a qualitative, descriptive, and exploratory approach, along with a literature review and field research. Data collection was carried out through semi-structured interviews conducted in February 2022. Results: A significant number of actions were observed, along with various accounts of the transformations that Entrepreneurial Education has brought about within and beyond UFFS, such as the impact of Empreende UFFS, which has already influenced more than 6,000 people. Additionally, the study identified involvement in the realm of education, with entrepreneurial education courses in 30% of UFFS undergraduate programs, eight research projects, and nine extension projects focused on Entrepreneurial Education. Conclusions: This signifies a scenario of cultural construction and transformation within the institution under study, as entrepreneurship becomes an agent of change and academic and social improvement at UFFS and in its operational region.